History Page: Leaders in MSK Radiology Augusto Pellegrini, 1877–1958 - Vanhoenacker, Filip M.; Bazzocchi, Alberto; Guglielmi, Giuseppe (Seminars in Musculoskeletal Radiology, 2023)
This history page in the series “Leaders in MSK Radiology” is dedicated to the memory and achievements of the Italian surgeon Augusto Pellegrini, whose name is partially associated with the medical eponym Pellegrini-Stieda disease.
Keywords: Pellegrini-Stieda disease; heterotopic calcification; history